PENERAPAN PENDEKATAN KETERAMPILAN PROSES UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI KELILING DAN LUAS LINGKARAN DI KELAS VIII AL BIRUNI SMP ISLAM TERPADU AL FAHMI PALU - Agung Wicaksono (Guru Tua : Jurnal Pendidikan dan Pembelajaran, 2019)
The purpose of this study was to obtain a description of the application of the process skills approach to improve student learning outcomes at materials circumference and area of circle in class VIII AL Biruni SMP IT Al Fahmi Palu. The design of this research is based on Kemmis dan Mc Taggart Model, it consisted of four components, (1) planning, (2) implementation of the action, (3) observation, and (4) reflection. Data collected in this research is in the form of data obtained from interviews, observations of teacher activities and student activities in the cycle I and cycle II, and the results of tests on a cycle I and cycle II. Based on research results, that applying Process Skill Approach which has 8 steps that is (1) heating, (2) observations, (3) interpretation of the observations, (4) forecasting, (5) Assessment, (6) generalizations discovery, (7) application and (8) communication with use worksheet at materials circumference and area of circle can to improve the results of student’s study class VIII AL Biruni SMP IT Al Fahmi Palu